Robust Governance as Catalyst of Digitalization of Human Capital - Farha, Mohd; Sheikh Annuar, Sh A Rahim (2021)
International organizations; be it the clients, consultants or contractors, face the gruelling task of acquiring the right talent for the job or risk cost over-run due to mismanaging resources while executing multiple projects simultaneously. Cost, time and quality of the completed product is governed by the ever changing demand and supply in this industry. This study was conducted in a Malaysian Oil and Gas company in the United Arab Emirates. The purpose of the study is to find a project governance matrix most suited for post-COVID environment. Qualitative findings analyse five key elements in resource management; namely manpower, tools, knowledge, skills, and experience. This paper will discuss a concise view of challenges faced in project management and suggests ways to develop the best approach in tackling the issues of the workforce. Findings indicate that the gaps studied have an equal correlation in producing optimal results. Project management systems demands continuity. Proper governance is the catalyst to a dynamic resource management and efficient project management. Interpretations and conclusions is suited for Oil and Gas project management, but generalized to suit other robust industries.